Antioxidant related to nutrition, stomatal density, and yield in cilantro (Coriandrum sativum L.) nourished with leachate from compost based on vegetable waste - D. D. Cruz Nieto; N. E. Muguruza Crispín; J. U. Romero Menacho; O. O. Osso Arriz; B. L. Mamani Salcedo; F. V. Luperdi Rios; C. P. Alvarez Quinteros; J. O. Nicho Vargas; M. I. Martinez Loli; R. W. Dextre Mendoza; M. N. Morales Alberto; C. M. Caira Mamani; et al. (Brazilian Journal of Biology)
Abstract The food crisis in Peru has intensified due to the increase in the costs of raw materials, such as energy sources, fertilizers, and other industrial inputs, as a result of global socioeconomic instability. For this reason, research was conducted on the antioxidant in relation to nutrition, stomatal density, and yield in cilantro nourished with compost leachate based on vegetable waste (CLPW). The objective was to analyze the antioxidants in relation to nutrition, stomatal density, and the yield of cilantro nourished with CLPW. The methodology was based on an applied experimental approach, so the statistical model of completely randomized block design was employed, which consisted of 3 blocks and 5 treatments: T1 with 0, T2 with 2, T3 with 3, T4 with 4, and T5 with 5 liters of CLPW per 200 liters of water. The doses were applied 15 and 30 days after planting. The data obtained from the physical characteristics of cilantro, such as total length, plant weight, number of leaves, and commercial yield, were processed using analysis of variance and the Duncan test. Additionally, the concentration of nutrients (nitrogen, potassium, phosphorus, calcium, magnesium, sulfur, molybdenum, iron, manganese, copper, zinc, boron, chlorides, and sodium), antioxidant capacity, stomatal density in leaves, and profitability were evaluated. The results determined that T5 stood out in total length with 55.23 cm, plant weight with 79.63 g, number of leaves with 162, and commercial yield with 27.017 t/ha. Regarding nutrient concentration, T5 stood out in calcium, magnesium, iron, boron, and chlorides, with a profitability of 334%. T4 stood out in antioxidant capacity with 4638.1 μmol Trolox/100 g sample, while T1 showed the highest stomatal density with 143 stomata/mm2. In conclusion, T4, with 4638.1 μmol Trolox/100 g sample, exhibited the highest antioxidant capacity. However, T5, with 4212.8 μmol Trolox/100 g sample, promoted greater nutrient absorption, lower stomatal density, and other biochemical reactions, which resulted in strengthening against environmental stress and, consequently, higher yield.